Nanomaterial Complexes Enriched With Natural Compounds Used in Cancer Therapies: A Perspective for Clinical Application - Saavedra-Leos, María Zenaida; Jordan-Alejandre, Euclides; López-Camarillo, César; Pozos-Guillen, Amaury; Leyva-Porras, César; Silva-Cázares, Macrina Beatriz (Frontiers in Oncology, 2021)
The resveratrol and quercetin are natural compounds content in many foods and beverages. Reports indicate implications for the health of general population, on the other hand the use of both compounds has interestingly results for treatment of many diseases as cardiovascular affections, diabetes, Alzheimer’s disease, viral and bacterial infections between others. Based on their capacities described as anti-inflammatory, antioxidant and anti-ageing, resveratrol and quercetin showed antiproliferative and anticancer activity specifically in maligned cells. These molecular characteristics trigger the pharmacological repurposed of both compounds and improved its research for treat different cancer types with interesting results at in vitro, in vivo and clinical trials studies. Meanwhile, the development of different systems of drug release in specific sites as nanomaterials and specifically the nanoparticles potentiate the personal treatment perspective, in conjunct with the actuals cancer therapies, regularly invasive and aggressive the perspective of nanomedicine higher effective and lower invasive has gained popularity. The knowledge of molecular interactions of resveratrol and quercetin in diseases confirm the evidence of multiple benefices, while the multiple analysis suggested a positive response for the treatment and diagnostics of cancer in different stages, including at metastatic stage. The present work reviews the reports related to the impact of resveratrol and quercetin in cancer treatment, and its effect when the antioxidants are encapsulated in different nanoparticle systems wich improve the prospects of cancer treatment.